Cloud IEC 61850: Architecture and Integration of Electrical Automation Systems - Lo, Thiago Berticelli; Mendes, Marcos Fonseca; Samaniego, Hugo A. Larangeira; Oliveira, Romulo Silva De (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2014)
The idea of using Virtualization and Cloud as the underlying infrastructure of electrical automation systems has been presented in literature but not properly evaluated. In this paper, a Physical to Virtual solution, or simply P2V approach, for a specific application case of a substation automatic voltage control (SAVC) is proposed in a simulated environment. Along with some fundamental IEC 61850 concepts, the paper presents the physical versus virtual mapping idea and the system requirements. From the logical design that describes the problem from the domain engineering perspective, the derived architecture design and main components are presented, followed by some implementation details and results obtained so far. The initial findings are that the solution can be closer to the logical design, and from the functional perspective, the virtualization approach of the IEC 61850 standard is possible. Performance issues, considering mainly metrics and measurements, are some of the challenges to be studied and assessed.